Concrete Compressive Strength, Flexural Strength, Tensile Strength Concrete Grades 25MPa, 30MPa, 35MPa and 40Mpa - Deuanhaksa, Surya; Vinh An, Le; Xuan Cay, Bui (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper is studying the value of compressive strength, flexural strength test, tensile strength test, according to the standard 25MPa (ratio cement1:sand1:stone2), 30MPa (ratio cement1: sand1.5:stone1.5), 35MPa (ratio cement1: sand0.75:stone1), and 40MPa (ratio cement1: sand0.25:stone0.75), and by using materials in the central part of the country, especially the province, where the materials used: cement, manufactured from the SAVANNAKHET cement factory , sand and river rocks and the building, (1). For testing the value of compressive strength concrete), size15cmx30 there are 12 samples here: (Concrete Grade 25MPa contains 3 examples, 30MPa concrete with 3 samples, 35MPa concrete with 3 samples, 40MPa concrete with 3 samples 28 days old. (2). For testing the value of tensile strength concrete), size15cmx15cmx15cm there are 12 samples here: (Concrete Grade 25MPa contains 3 examples, 30MPa concrete with 3 samples, 35MPa concrete with 3 samples, 40MPa concrete with 3 samples 28 days old. (3). For testing the value of flexural strength concrete), Size 15cmx15cmx60cm contains 12 samples here: (Concrete Grade 25MPa contains 3 samples, 30MPa concrete with 3 samples, 35MPa concrete with 3 samples, 40MPa concrete with 3 samples 28 days old, for testing the value of tensile strength concrete) given to a Standard AASHTO(American Association of State Highways and Transportation Officials Test), ASTM (American Society for Testing and Materials)... with the age of 28 days respectively, it is then tested with a mechanical machine to find the unit value to analyze the value of compressive strength, flexural strength test, tensile strength test.